The pedagogical practices of Québec high school teachers relative to sexual diversity - Richard, Gabrielle (Journal of LGBT Youth, 2015)
This article explores the ways in which teachers describe their pedagogical and intervention practices relative to sexual diversity in Québec (Canada). Three variables closely associated with teachers who report inclusive practices emerge: experiential training (based on the experience of a lesbian, gay, or bisexual [LGB] teacher), contact training (from close acquaintance with LGB individuals), and professional training. These factors impact the probability that a teacher will refer to homosexuality, intervene when homophobic incidents occur to deconstruct prejudices, and become the confidant of LGBQ students. Results are discussed based on research on minority teachers and on the roles of straight allies in education.
Keywords: EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; diversité sexuelle; formations; homophobie; hétérosexisme; identités LGBTQIA2+; outils; québec; ressource en ligne; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; école secondaire

Project Implicit
Test de préjugés inconscients
Keywords: approches et analyses; biais inconscients; cours; discipline; discours dominant; formations; inégalités; outils; pol5480; premier cycle; privilèges; psychologie; pédagogie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences